Evaluative methodology of compliance with the competences of students oriented towards the graduation profile - Aravena, Margarita; Berrios, Alejandro; Figueroa, Viana Ulda (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
Evaluating the achievement of profiles is part of the constant management of tertiary level institutions, this must be constantly socialized and communicated in the organic structure of the institution. Carrying out evaluations of student competencies implies creating evaluative milestones, which must be constantly advised, accompanied and supervised, the milestones help to obtain feedback that is born from constant evaluation, nurtured, oriented and complemented by monitoring graduates. This allows us to generate future adjustments to the graduate profile.